2018
DOI: 10.3389/fmicb.2018.01348
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin Restricts Social Cheating in Pseudomonas aeruginosa

Abstract: Quorum sensing (QS) in Pseudomonas aeruginosa coordinates the expression of virulence factors, such as exoproteases and siderophores, that are public goods utilized by the whole population of bacteria, regardless of whether they invested or not in their production. These public goods can be used by QS defective mutants for growth, and since these mutants do not contribute to public goods production, they are considered social cheaters. Pyocyanin is a phenazine that is a toxic, QS-controlled metabolite produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…These authors noticed that the pyocyanin was exhibited as a tremendous growth inhibiting agent against M. phaseolina and could suppress the associated diseases very effectively at low concentration, and the inhibitory action of 100 µl of purified pyocyanin against various phytopathogens and saprophytic molds was also reported 36 . The quorum sensing P. aeruginosa producing pyocyanin is correlated with siderospores activity that possesses antibacterial property 37 . In another independent research, it was observed that the phenazin pigment 50 µg produced by P. aeruginosa inhibit the growth of Candida albicans and Aspergillus fumigatus fungal growth 38 .…”
Section: Discussionmentioning
confidence: 99%
“…These authors noticed that the pyocyanin was exhibited as a tremendous growth inhibiting agent against M. phaseolina and could suppress the associated diseases very effectively at low concentration, and the inhibitory action of 100 µl of purified pyocyanin against various phytopathogens and saprophytic molds was also reported 36 . The quorum sensing P. aeruginosa producing pyocyanin is correlated with siderospores activity that possesses antibacterial property 37 . In another independent research, it was observed that the phenazin pigment 50 µg produced by P. aeruginosa inhibit the growth of Candida albicans and Aspergillus fumigatus fungal growth 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, P. aeruginosa and other bacteria have genetically encoded mechanisms that can deter social cheating (10,27,28). For example, the redox-active phenazine pyocyanin restricts social cheating in P. aeruginosa by selecting for individuals with intact QS systems, which are required to induce antioxidant defense systems that offset phenazine toxicity (29).…”
mentioning
confidence: 99%
“…Virulence factors as pyocyanin production, biofilm and motility are regulated by QS and also influenced by the phage infections (Morkunas et al, 2012;Hosseinidoust et al, 2013;Latino et al, 2014;Castañeda-Tamez et al, 2018;Tariq et al, 2019). The infection with the wild type phage, AUS531phi, carrying the bci gene, increased the production of virulence factors, pyocyanin and biofilm, whose presence is characteristic in the lung of CF patients (Castañeda-Tamez et al, 2018). The increase in both biofilm and pyocyanin and a reduction in the swarming motility, are a response to the phage infection which is higher when the bci gene is present, but also due to the integration of the temperate phage and the bci gene in the bacterial genome, as was described previously.…”
Section: Discussionmentioning
confidence: 99%